How Does the Visualization Technique Affect the Design Process? Using Sketches, Real Products and Virtual Models to Test the User’s Emotional Response. - Alonso García, María; Palacios Ibáñez, Almudena; de Cózar Macías, Óscar D.; Marín Granados, Manuel D. (International Journal of Interactive Multimedia and Artificial Intelligence, 2024)
Testing products during the design process can help design teams anticipate user needs and predict a positive emotional response. Emerging technologies, e.g., Virtual Reality (VR), allow designers to test products in a more sophisticated manner alongside traditional approaches like sketches, photographs or physical prototypes. In this paper, we present the results of a study conducted to evaluate the feasibility of seven visualization techniques for product assessment within the framework of emotional design, suggesting that the user’s perception depends on the visualization technique used to present the product. This research provides recommendations for product evaluation using physical, virtual, or conceptual prototypes to analyze the user’s emotional response throughout 19 parameters. Our results indicate that the use of virtual environments, including VR and VR with Passive Haptics (VRPH), can facilitate user participation in the design process, although these visualization techniques may also exaggerate the emotions perceived by users. In this context, VRPH tends to overstate the tactile perception of the product. Additionally, our results reveal that both virtual and conceptual environments can amplify a user’s likelihood to purchase a product. However, the latter setting could also potentially lead to confusion among users in regards to their perception of the product’s weight, dimensions, and cost. Based on these findings, the authors encourage industrial designers to develop new methodologies to optimize design process and minimize costs.